KAJIAN POLA CURAH HUJAN DURASI PANJANG TERKAIT DENGAN WAKTU KEJADIAN BANJIR DI KABUPATEN ACEH UTARA - Azwar Azwar; Ella Meilianda; Masimin Masimin (Prodi Magister Teknik Sipil Unsyiah, 2021)
North Aceh Regency almost every year experiences flooding due to heavy rains, both due to rain in the area and flooding of shipments due to heavy rains in neighboring districts namely Bener Meriah. Judging from the time of the incident, heavy rains always occur in the final months of each year. The duration of rainfall is two, namely: (a) short duration and (b) long duration. The second limit is the duration of rain 24 hours (1 day), so that the duration of rainfall is long if the time of occurrence is longer than 24 hours. For tropical climates such as the Aceh region known to experience two seasons, namely: a) the rainy season and b) the dry season in terms of climatology, the rainy season is identical to the occurrence of flooding. The dry season or rainy season are related to the time of year, for example the flood season occurs in the final months of each year, the dry season occurs in the middle of the year, especially for the North Aceh region. The objectives of this study are (a) to obtain information on the relatively heavy rainfall distribution pattern for long duration rainfall events, namely 1-day, 3-day, 5-day and 7-daily. (b) Knowing the timing of flood events is calculated based on the movement of the sun. The data used is daily rainfall data obtained from the Lhokseumawe Meteorological Station from 1986 to 2016. The results of the analysis are to find out the maximum rainfall for 1-day, 3-day, 5-day, and 7 daily. Because what was investigated was the pattern of rain, the partial series method was used, namely the possibility of some data being taken in one year. The results of processing data show that the highest incidence of 1-day maximum rainfall occurs in the IV quadrant or week 52 which is equal to 45.9%, in this case the highest number of flood events will occur when the sun moves towards the south. To identify heavy rain events that can cause flooding based on station rainfall data correlated with debits recorded on AWLR (Automatic Water Level Recorder). From the results of the identification that there was an increase in river discharge in November and December.